Card Sort Strategy: Does It Have an Effect on Students’ Writing Achievement at SMP Negeri 9 Kendari? - Samirin, Endang Tri Novianty; Mursalim, Mursalim; Siam, Siam (Journal of Teaching of English, 2021)
The objective of this study is to find out the effect of card sort strategy on students’ writing achievement at SMP Negeri 9 Kendari. This study used quasi experimental design that consisted of experimental class and control class. The sample of this study was students at class VIII4 and VIII5 at SMPN 9 Kendari in academic years 2019/2020. The sample was taken by using cluster random sampling and the total number of students was 62, 31 was for experimental class (VIII4) and 31 was for control class (VIII5). Instrument of the study was a writing test that focused on descriptive text. The writer collected the data by giving pre-test in both of the classes, giving treatment in experimental by giving card sort strategy and non-card sort strategy in control class, and giving post-test in both classes. For testing hypothesis, the researcher used independent sample t-test calculated through SPSS 16.0. The findings of this study showed that students’ mean score of post-test in experimental class was 60.45. It increased 8.19 point from its pre-test (52.26), while students’ mean score of post-test in control class was 54.32. It increased 3.72 point from its pre-test (50.60). Besides, the value of degree of freedom (df) was 60, t value was 9.101, and sig (2 tailed) value was 0.000. It means that the probability (sig) value was lower than α ( p value < α or 0.000 < 0.05). It indicated that, card sort strategy had a significant effect on students’ writing achievement at eight-grade of SMPN 9 Kendari.